(3JbjjO Ydi GdSde GdeQhfbs - (3SYjO Hf EHQGgje bOhQI GdLRGFQis; (3YHO GdQMef Hf eMeO GdUZjQs ((3GdSGdc Hf SjOi CMeO Hf eHGQc s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde GdEfSGf ef MbGFb GdJUhQGJ eGde jcf jYde hHYO , aEfi ESJNQJ Gddg ai hVY JbjjO Ydi GdCQLhRI GdehSheI H(B" (3GdSde GdeQhfb ai Yde Gd efWb (B" (3HMjK jchf eVGakG dTQM GdeUfa cGdJPjjd deG CZadg GdfGXe ai TQMI s
(3BNQgG (B:s
(3hef GdNdd ai UhQI GdbjGS GdG jhLO eMehd GdUZQi JGeG ai VhYI GdcHQI , fMh (B: (3GdEfSGf dg TYQ , hcd TQ jfHJ , jfJL (B: (3GdEfSGf jfHJ hgh cGPH GfJgi gPG GdeDda s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdadSaI hGdefWbs